On-Site Upgrading : Strategi Memenuhi Adequate Housing di Kampung Kota - Sekar Ari Utari; Dwita Hadi Rahmi; Ikaputra . (Unika Soegijapranata Semarang, 2020)
Housing and settlement conditions are still things that need to be resolved in Indonesia. Settlements in many cities in Indonesia still have many shortcomings in terms of physical conditions and basic infrastructure. The government has tried a method to overcome this problem through the Kampung Improvement Program (KIP). However, KIP has not been able to solve the problem whose effects are sustainable. There are still many urban poor living in slums urban areas. Given the above understanding, there is an urgency to look into a method to solve the problems. On-site upgrading is a step that can be used as a method for solving Kampung problems in Indonesia. This paper examines what and how the concept of on-site upgrading can provide sustainable effects in Indonesia.